A Clinic-Radiomics Model for Predicting the Incidence of Persistent Organ Failure in Patients with Acute Necrotizing Pancreatitis - Nan Liu; Yidong Wan; Yifan Tong; Jie He; Shufeng Xu; Xi Hu; Chen Luo; Lei Xu; Feng Guo; Bo Shen; Hong Yu (Gastroenterology Research and Practice)
Background. Persistent organ failure (POF) is the leading cause of death in patients with acute necrotizing pancreatitis (ANP). Although several risk factors have been identified, there remains a lack of efficient instruments to accurately predict the incidence of POF in ANP. Methods. Retrospectively, the clinical and imaging data of 178 patients with ANP were collected from our database, and the patients were divided into training (n=125) and validation (n=53) cohorts. Through computed tomography image acquisition, the volume of interest segmentation, and feature extraction and selection, a pure radiomics model in terms of POF prediction was established. Then, a clinic-radiomics model integrating the pure radiomics model and clinical risk factors was constructed. Both primary and secondary endpoints were compared between the high- and low-risk groups stratified by the clinic-radiomics model. Results. According to the 547 selected radiomics features, four models were derived from features. A clinic-radiomics model in the training and validation sets showed better predictive performance than pure radiomics and clinical models. The clinic-radiomics model was evaluated by the ratios of intervention and mechanical ventilation, intensive care unit (ICU) stays, and hospital stays. The results showed that the high-risk group had significantly higher intervention rates, ICU stays, and hospital stays than the low-risk group, with the confidence interval of 90% (p<0.1 for all). Conclusions. This clinic-radiomics model is a useful instrument for clinicians to evaluate the incidence of POF, facilitating patients’ and their families’ understanding of the ANP prognosis.